ACCRUAL EARNING MANAGEMENT AND FIRM VALUE : THE MODERATING ROLE OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) PERFORMANCE - Hayati Fatimah; Ridwan Zulpi Agha; Riky Rizki Junaidi (Universitas Tulungagung, 2026)
This study aims to analyze the relationship between accrual earnings management and firm value, with environmental, social, and governance (ESG) performance serving as a moderating variable, based on agency theory. The sample consists of manufacturing companies listed on the Indonesia Stock Exchange during the period 2022–2024. Regression analysis is employed to test the proposed hypotheses. The findings indicate that accrual earnings management is significantly and negatively associated with firm value. Furthermore, ESG performance weakens the negative relationship between accrual earnings management and firm value. These findings remain robust across additional analyses in which ESG performance is decomposed into its environmental, social, and governance dimensions. Specifically, environmental performance weakens the negative relationship between accrual earnings management and firm value. Likewise, social performance weakens the negative relationship between accrual earnings management and firm value. Similarly, governance performance weakens the negative relationship between accrual earnings management and firm value. The findings of this study provide important implications for firms, financial statement users, and the Indonesian Financial Services Authority (OJK).